Fibroblast growth factor 2 is an intrinsic chondroprotective agent that suppresses ADAMTS-5 and delays cartilage degradation in murine osteoarthritis. - Chia, S; Sawaji, Y; Burleigh, A; McLean, C; Inglis, J; Saklatvala, J; Vincent, T (2009)
OBJECTIVE: We have previously identified in articular cartilage an abundant pool of the heparin-binding growth factor, fibroblast growth factor 2 (FGF-2), which is bound to the pericellular matrix heparan sulfate proteoglycan, perlecan. This pool of FGF-2 activates chondrocytes upon tissue loading and is released following mechanical injury. In vitro, FGF-2 suppresses interleukin-1-driven aggrecanase activity in human cartilage explants, suggesting a chondroprotective role in vivo. We undertook this study to investigate the in vivo role of FGF-2 in murine cartilage. METHODS: Basal characteristics of the articular cartilage of Fgf2(-/-) and Fgf2(+/+) mice were determined by histomorphometry, nanoindentation, and quantitative reverse transcriptase-polymerase chain reaction. The articular cartilage was graded histologically in aged mice as well as in mice in which osteoarthritis (OA) had been induced by surgical destabilization of the medial meniscus. RNA was extracted from the joints of Fgf2(-/-) and Fgf2(+/+) mice following surgery and quantitatively assessed for key regulatory molecules. The effect of subcutaneous administration of recombinant FGF-2 on OA progression was assessed in Fgf2(-/-) mice. RESULTS: Fgf2(-/-) mice were morphologically indistinguishable from wild-type (WT) animals up to age 12 weeks; the cartilage thickness and proteoglycan staining were equivalent, as was the mechanical integrity of the matrix. However, Fgf2(-/-) mice exhibited accelerated spontaneous and surgically induced OA. Surgically induced OA in Fgf2(-/-) mice was suppressed to levels in WT mice by subcutaneous administration of recombinant FGF-2. Increased disease in Fgf2(-/-) mice was associated with increased expression of messenger RNA of Adamts5, the key murine aggrecanase. CONCLUSION: These data identify FGF-2 as a novel endogenous chondroprotective agent in articular cartilage.